IMPLEMENTASI NILAI KEBANGSAAN BERSUMBER PADA UUD 1945 TERHADAP KEAMANAN DATA PRIBADI PADA MEDIA SOSIAL - Winda Aulya; Edy Soesanto, Lisky Fhatimah (Jurnal Komunikasi, 2024)
The rapid development of digital technology has made it easier for users from time to time. Social Media has become a part of everyday life to get, share and disseminate information. One of the negative impacts of using social media is the leaking of personal information and the loss of privacy of social media users. Information system security is an asset that needs to be protected. Especially in Indonesia, laws related to this issue need to be implemented properly. Indeed, there are some scattered provisions on privacy and personal data protection in various laws and regulations in Indonesia, which are not enough to facilitate the development of Indonesia's digital economy. The method used in this study is to use literature studies and descriptive analysis this study aims to clarify the concept of law enforcement in Indonesia and the application of law to the security of data privacy of social media users